Measuring the social value of innovation a link in the university technology transfer and entrepreneurship equation - Libecap, Gary D. (Advances in the study of entrepreneurship, innovation and economic growth ;, 2009)
This volume presents a series of perspectives that evaluate the merits of and potential for establishing institutionalized social valuation protocols within university settings. The volumes open with a comprehensive overview of the existing literature that addresses issues related to assessing the social value of university innovations. The first section provides sociological, organizational, and economic perspectives on issues informing the forecasting and/or demonstrating the social value of university innovations. The second section explores potential metrics and measures for either forecasting or demonstrating the social and economic value of university innovations. The third section concludes by considering issues of governance over and the organizational positioning institutionalized protocol for forecasting and demonstrating the social and economic value of university innovations.